2021
DOI: 10.1021/acsami.1c04925
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinnable, Neutral Coacervates for Facile Preparation of Solid Phenolic Bioadhesives

Abstract: Liquid–liquid phase separation in an aqueous polymer solution is a unique physicochemical phenomenon, and the material present in the dense bottom layer is called a coacervate. A partial degree of water exclusion during coacervate formation often results in adhesive properties. The high viscosity makes coacervates incompatible with electrospinning processes. Coacervates can be electrospinnable only when the viscosity level of coacervates is adjusted. Electrospinning of coacervates results in a liquid-to-solid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…It can also be synthesized using sugar through multistep enzymatic reactions . As an important bioactive molecule, catechin (CA) can exert the effects of antisepsis, antioxidation, anticancer, and hemostasis. Very recently, analogous polyphenol compounds have been used to prepare multiple underwater medical adhesives. Wherein, phenolic hydroxyl groups were regarded as donors of hydrogen bond to interact with other components containing hydrogen-bond acceptors. Interestingly, they have not yet been considered for the preparation of solvent-free supramolecular adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…It can also be synthesized using sugar through multistep enzymatic reactions . As an important bioactive molecule, catechin (CA) can exert the effects of antisepsis, antioxidation, anticancer, and hemostasis. Very recently, analogous polyphenol compounds have been used to prepare multiple underwater medical adhesives. Wherein, phenolic hydroxyl groups were regarded as donors of hydrogen bond to interact with other components containing hydrogen-bond acceptors. Interestingly, they have not yet been considered for the preparation of solvent-free supramolecular adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…(B) Blood loss of hemostatic gauzes [ 83 ] . (C) Effect of nanofiber weight on mass and the time of bleeding [ 152 ] . (D) Effects of fiber diameter on mechanical properties [ 91 ] .…”
Section: Micro/nanostructures In Hemostatic Applicationmentioning
confidence: 99%
“…Importantly, the electrospun NFMs must be water-resistant to take advantage of the morphology of the nanofibers. For example, Cui et al reported a PVA–TA nanofiber, but the mixing ratio of TA to PVA was only 0.2:1, and Kim et al prepared a PVA NFM containing a large amount of TA, but this was immediately converted to the coacervate state upon contact with water …”
Section: Introductionmentioning
confidence: 99%
“…For example, Cui et al reported a PVA−TA nanofiber, but the mixing ratio of TA to PVA was only 0.2:1, 20 and Kim et al prepared a PVA NFM containing a large amount of TA, but this was immediately converted to the coacervate state upon contact with water. 21 Herein, we report a NFM-based face mask filter composed of PVA and TA in a weight ratio of 1:0.5. To enable green electrospinning, the formation of strong hydrogen bonds between PVA and TA was partially inhibited using a mixed solvent of water/ethanol, and the resultant solution was homogeneous without any aggregation or precipitation.…”
Section: ■ Introductionmentioning
confidence: 99%